2009
DOI: 10.1128/iai.00454-09
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dendritic Cells and Alveolar Macrophages in Regulating Early Host Defense against Pulmonary Infection withCryptococcus neoformans

Abstract: Successful pulmonary clearance of the encapsulated yeast Cryptococcus neoformans requires a T1 adaptive immune response. This response takes up to 3 weeks to fully develop. The role of the initial, innate immune response against the organism is uncertain. In this study, an established model of diphtheria toxin-mediated depletion of resident pulmonary dendritic cells (DC) and alveolar macrophages (AM) was used to assess the contribution of these cells to the initial host response against cryptococcal infection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
103
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 80 publications
4
103
0
2
Order By: Relevance
“…[25][26][27][28][29] Yet, AMs also protect against deleterious and ineffective inflammation before the onset of adaptive immunity. 30 Previous studies 31,32 identified macrophage accumulation in the lungs of cryptococcal-infected mice during the effector phase (approximately 14 -28 dpi) of the host response. Impaired cryptococcal clearance in chemokine receptor 2 (CCR2)-deficient mice correlates strongly with diminished pulmonary macrophage accumulation.…”
mentioning
confidence: 99%
“…[25][26][27][28][29] Yet, AMs also protect against deleterious and ineffective inflammation before the onset of adaptive immunity. 30 Previous studies 31,32 identified macrophage accumulation in the lungs of cryptococcal-infected mice during the effector phase (approximately 14 -28 dpi) of the host response. Impaired cryptococcal clearance in chemokine receptor 2 (CCR2)-deficient mice correlates strongly with diminished pulmonary macrophage accumulation.…”
mentioning
confidence: 99%
“…he interaction of the human pathogenic fungus Cryptococcus neoformans with macrophages is thought to be a key event in the outcome of cryptococcal infection (10,13,17,28,29). C. neoformans is a facultative intracellular pathogen and, once within a macrophage, C. neoformans can replicate intracellularly with outcomes that range from host cell lysis to nonlytic exocytosis (2,3,23).…”
mentioning
confidence: 99%
“…Dendritic cells function as major antigenpresenting cells that constantly monitor the current antigen population and modulate adaptive immune responses accordingly (28). During cryptococcal infections, DCs are thought to be the major initiators of protective cell-mediated immunity (11,147). Not only are major antigens (e.g., mannoproteins and glycoantigens) for the activation of anticryptococcal T-cell responses dominantly presented by DCs (107,125), but also the induction of T-cell responses by DCs is much more efficient than by alveolar or peritoneal macrophages (125,180).…”
mentioning
confidence: 99%